Pemberian Perlindungan Hukum Pekerja Atas Pelanggaran Perjanjian Kontrak Kerja Oleh Dinas Tenaga Kerja Kabupaten Bintan: (Studi Kasus PT. Sumber Izumi Mas Perkasa Bintan) - Roha Purnama Putri; Rapika Rapika; Tito Raman Dhanni; Mellyana Candra (Fakultas Teknik Universitas Cenderawasih, 2023)
This article examines the provision of legal protection to workers who violate work contract agreements through the Bintan Regency Manpower Service. The case study was conducted at PT. Sumber Izum Mas Perkasa Bintan. This paper aims to analyze the legal protection of workers in violation of employment contracts against workers' rights and the effectiveness of legal protection provided by the Manpower Service, as well as providing recommendations for improving worker protection regarding employment contract agreements in the Bintan Region. This research was conducted in a qualitative descriptive manner, namely describing the results of interviews, observations and direct observations, as well as using literature studies through relevant sites and articles. The results of this research require increasing legal awareness in companies and workers. Apart from that, the Manpower Department needs to strengthen law enforcement to prevent violations of employment contracts.